2012
DOI: 10.3109/14767058.2011.644365
|View full text |Cite
|
Sign up to set email alerts
|

The assessment of time-dependent myocardial changes in infants with perinatal hypoxia

Abstract: These findings demonstrated that the signs of myocardial damage due to perinatal hypoxia still present at first month.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 21 publications
1
7
0
1
Order By: Relevance
“…Indices of depressed cardiac function in this study parallel previously reported consequences of developmental hypoxia or intrauterine growth restriction in the sheep and human heart (6,22,29), suggesting that placental and maternal factors are not primarily responsible for cardiovascular adaptations to this stress. We found that developmental hypoxia decreased ⌬P/ ⌬t Max and increased , similar to findings from prior studies of the isolated, Langendorff-perfused fetal chicken heart at 90% of incubation (day 19; 38), and isolated muscle bundles from the 95% incubation (day 20) hypoxia-incubated chicken heart (48).…”
Section: Cardiac Functionsupporting
confidence: 86%
See 1 more Smart Citation
“…Indices of depressed cardiac function in this study parallel previously reported consequences of developmental hypoxia or intrauterine growth restriction in the sheep and human heart (6,22,29), suggesting that placental and maternal factors are not primarily responsible for cardiovascular adaptations to this stress. We found that developmental hypoxia decreased ⌬P/ ⌬t Max and increased , similar to findings from prior studies of the isolated, Langendorff-perfused fetal chicken heart at 90% of incubation (day 19; 38), and isolated muscle bundles from the 95% incubation (day 20) hypoxia-incubated chicken heart (48).…”
Section: Cardiac Functionsupporting
confidence: 86%
“…Hypoxic stress during development has been investigated in a number of vertebrate models (6,18,32,46). Chronic fetal hypoxia has been linked to depressed fetal cardiac function in mammals (15,18,32,37) and is predictive of cardiovascular disease states later in life (16,26,27).…”
Section: Perspectives and Significancementioning
confidence: 99%
“…Noncardiac disease, such as perinatal hypoxemia, persistent pulmonary hypertension, and sepsis, may be associated with cardiovascular biomarkers. [48][49][50] Gestational age plays a role in NT-proBNP levels, as demonstrated in premature neonates with and without PDA (the pattern of NT-proBNP levels is higher in neonates with PDA than in those in whom the PDA is closed), and NT-proBNP levels seem to follow a similar postnatal pattern in term neonates (in whom the levels decline over the first few days of life). 51,52 We did not recruit premature neonates or those who required neonatal inpatient care, populations in which the new test warrants further evaluation.…”
Section: Discussionmentioning
confidence: 91%
“…Cetin et al ( 43 ) highlighted that the plasma BNP concentration in children with perinatal asphyxia on the first postpartum day was significantly higher than that in the control group, suggesting that BNP could be used as an indicator for the diagnosis of neonatal asphyxia. Jiang et al ( 42 ) drew similar conclusions, showing that the plasma BNP concentration at 12 h postpartum in the asphyxia group was significantly higher than that in the control group without asphyxia and myocardial injury.…”
Section: Manuscript Formattingmentioning
confidence: 99%